2014
DOI: 10.1155/2014/614187
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Essential Oil and Extracts ofValeriana jatamansiRoots

Abstract: Valeriana jatamansi is an indigenous medicinal plant used in the treatment of a number of diseases. In the present study, chemical composition of the essential oil was determined by GC-MS. Seven major components were identified in Valeriana jatamansi essential oil, namely, β-vatirenene, β-patchoulene, dehydroaromadendrene, β-gurjunene, patchoulic alcohol, β-guaiene, and α-muurolene. Methanolic, aqueous, and chloroform extracts of Valeriana jatamansi roots were also prepared and analyzed for their polyphenols a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…The values of IC 50 were in the order: gallic acid < querecetin < tannic acid < ascorbic acid < essential oil samples of the species. Similarly, Thusoo et al (33) found IC 50 value of V. jatamansi as 876 μg/mL by using DPPH assay collected from Jammu and Kashmir region of Himalaya. Antioxidant activity analyzed by FRAP assay from the plant material of V. jatamansi from Khasi Hills of eastern Himalaya (12) essential β-selinene and α-guaiene were recorded higher in winter followed by spring and summer season.…”
Section: Antioxidant Activity Of Essential Oil Samplesmentioning
confidence: 89%
“…The values of IC 50 were in the order: gallic acid < querecetin < tannic acid < ascorbic acid < essential oil samples of the species. Similarly, Thusoo et al (33) found IC 50 value of V. jatamansi as 876 μg/mL by using DPPH assay collected from Jammu and Kashmir region of Himalaya. Antioxidant activity analyzed by FRAP assay from the plant material of V. jatamansi from Khasi Hills of eastern Himalaya (12) essential β-selinene and α-guaiene were recorded higher in winter followed by spring and summer season.…”
Section: Antioxidant Activity Of Essential Oil Samplesmentioning
confidence: 89%
“…In another experiment, 27 compounds were identified in the roots oil of V. jatamansi including patchoulol ( 247 ), α‐bulnesene ( 236 ), isovaleric acid ( 218 ), α‐guaiene ( 237 ), and 3‐methylvaleric acid ( 233 ) as the major compounds using GC–MS (Thusoo et al, ). Raina and Negi () studied 21 compounds in the oil isolated from roots of V. jatamansi by GC and GC–MS.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…DPPH assay has been extensively used for screening plant extracts because of its sensitivity to detect active ingredients at low concentrations 25 . The proton radical scavenging action is one of the various mechanisms for measuring antioxidant activity.…”
Section: Results and Discussion: 1 1-diphenyl-2-picrylhydrazyl (Dpphmentioning
confidence: 99%